MANAJEMEN ISLAM DALAM PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) PADA PENDIDIKAN ISLAM - Dwi Budiarto; Syamsiani (Al-Wihdah: Jurnal Pendidikan Islam, 2026)
Abstract The rapid development of Artificial Intelligence (AI) has fundamentally transformed various aspects of human life, including the field of Islamic education. This study aims to analyze the implementation of Islamic management principles in the utilization of AI within Islamic educational institutions. Employing a qualitative approach with library research design, this study examines relevant literature including books, journal articles, proceedings, and policy documents related to Islamic education management and AI integration. The findings reveal that Islamic management principles—namely tawhid (monotheism), amanah (trustworthiness), justice ('adl), and ihsan (excellence)—can serve as a foundational framework for governing AI utilization in educational settings. AI has been demonstrated to enhance learning efficiency, personalize instruction, and streamline administrative processes. However, its application necessitates robust supervision grounded in Islamic values to prevent ethical violations, academic dishonesty, and the erosion of pedagogical-spiritual relationships between educators and students. This study concludes that the integration of AI in Islamic education must be conducted wisely and strategically to ensure that technological advancement does not compromise the essence of moral and character formation, which remains the core objective of Islamic education. Keywords: Islamic Management, Artificial Intelligence, Islamic Education, Technology Ethics, Maqasid Shariah.